Impact of functional, morphological and clinical parameters on epicardial adipose tissue in patients with coronary artery disease - Dösch, Christina; Haghi, Dariusch; Süselbeck, Tim; Schönberg, Stefan; Borggrefe, Martin; Papavassiliu, Theano (Circulation journal, 2012)
Japan's largest platform for academic e-journals: J-STAGE is a full text database for reviewed academic papers published by Japanese societies